2021
DOI: 10.3389/fpsyg.2021.784752
|View full text |Cite
|
Sign up to set email alerts
|

Phrase Depicting Immoral Behavior Dilates Its Subjective Time Judgment

Abstract: Intuitive moral emotions play a major role in forming our opinions and moral decisions. However, it is not yet known how we perceive the subjective time of moral-related information. In this study, we compared subjective durations of phrases depicting immoral, disgust, or neutral behaviors in a duration bisection task and found that phrases depicting immoral behavior were perceived as lasting longer than the neutral and disgusting phrases. By contrast, the subjective duration of the disgusting phrase, unlike t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The trial began with an 800‐ms white fixation point (“+”), followed by a blank screen, lasting for 400 to 600 ms. A facial image, of either an infant or an adult, was then displayed for a randomly chosen probe duration (options: 400, 500, 600, 700, and 800 ms). The set of durations was selected based on past research for better comparison (duration selection referenced from Droit‐Volet et al, 2010 ; Jia, et al, 2021 ; Shi et al, 2012 ). A 500‐ms blank screen ensued, and then a white question mark appeared.…”
Section: Methodsmentioning
confidence: 99%
“…The trial began with an 800‐ms white fixation point (“+”), followed by a blank screen, lasting for 400 to 600 ms. A facial image, of either an infant or an adult, was then displayed for a randomly chosen probe duration (options: 400, 500, 600, 700, and 800 ms). The set of durations was selected based on past research for better comparison (duration selection referenced from Droit‐Volet et al, 2010 ; Jia, et al, 2021 ; Shi et al, 2012 ). A 500‐ms blank screen ensued, and then a white question mark appeared.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies focused on the association of moral decision-making and textual information found that people who are high on the Care dimension are faster in the recognition of words of high moral valence compared to neutral words (Yang et al, 2017). Moreover, previous studies have indicated that people need longer time for decision-making when presented with messages which are perceived to have immoral content (Gantman et al, 2020; Jia et al, 2021), and that for that phenomenon there is a biological basis (Heekeren et al, 2005). However, the moral foundations theory has never been tested in the context of research integrity and research ethics, where moral foundations could be considered a decisive factor in the recognition of inappropriate research behaviors.…”
Section: Introductionmentioning
confidence: 99%